Clinical predictors of depressive symptom remission and response after racemic ketamine and esketamine infusion in treatment‐resistant depression. (18th February 2022) - Jesus‐Nunes, Ana Paula; Leal, Gustavo C.; Correia‐Melo, Fernanda S.; Vieira, Flávia; Mello, Rodrigo P.; Caliman‐Fontes, Ana Teresa; Echegaray, Mariana V. F.; Marback, Roberta F.; Guerreiro‐Costa, Lívia N. F.; Souza‐Marques, Breno; Santos‐Lima, Cassio; Souza, Lucca S.; et al.
Abstract: Background: Major depressive disorder (MDD) is a leading cause of disability worldwide and most people do not achieve symptom remission. Treatment‐resistant depression (TRD) is characterized by the failure of at least one adequate trial of a major class of antidepressant, with adequate time and dosage. We aimed to identify clinical predictors of depressive symptom remission and response 24 h and 7 days after racemic ketamine and esketamine infusions. Methods: A randomized, double‐blind, active‐controlled, non‐inferiority trial using ketamine and esketamine in TRD. Individuals diagnosed with MDD according to Diagnostic and Statistical Manual of Mental Disorders version IV and fulfilling TRD criteria were recruited from March 2017 to June 2018. Participants received a single subanesthetic dose of ketamine (0.5 mg/kg) or esketamine (0.25 mg/kg) for 40 min. Depressive symptoms were assessed using the Montgomery‐Åsberg Depression Rating Scale (MADRS) and symptom remission was defined as a MADRS score ≤7 and response defined as ≥50% reduction in depressive symptom severity, 24 h and 7 days after the infusion. Clinical variables were selected based on previous clinical trials. Stepwise backward logistic regression was used, considering a confidence level of 95%. Results: 61 subjects were included: 39 (63.9%) were females with a mean age of 47.2 ± 14.9. Higher number of therapeutic failures (Odds Ratio (OR) = 0.677; 95% confidence interval (CI): 0.47–0.97) and higher severity of illness (OR = 0.912; 95% CI: 0.83–0.99) were associated with fewer remissions of depressive symptoms 7 days after intervention, and with fewer response in 24 h (OR = 0.583; 95% CI: 0, 40; 0, 84 and OR = 0.909; 95% CI: 0, 83; 0, 99, respectively). Conclusion: Number of treatment failures and severity of illness were predictors of fewer remissions and responses of depressive symptoms in this TRD population. Study of predictors of remission may contribute to better selection patients that may benefit from receiving ketamine.